(untitled) (International Journal of Food and Nutritional Sciences, 2021)
This is a small handheld tool used for turning bolts and screws which have hexagonal sockets. Many people assume that Allen keys are new, but to surprise, these tools are fairly old. The concept of a hexagonal-shaped screwdriver came in the mid-to-late 1800s and became popular. Now they are available in different sizes. According to our research, the existing products have a lot of problematic issue compared to our product